Factors affecting purchasing decision for female fashion clothes of online social media on facebook in Bangkok, Thailand - Pimchanok Aramrungroj (Prince of Songkla University., 2016)
Thesis (M.B.A., Business Administration)--Prince of Songkla University, 2015